Tourism and the visit rate in the tourism regions in Eastern Slovakia from the point of selected indicators - Klamár, Radoslav (Bulletin of Geography. Socio-economic Series, 2014)
The submitted paper deals with the problem of tourism development and the visit rate in the selected region of Eastern Slovakia consisting of six specified tourism regions. The individual regions are briefly presented from the perspective of their potential for the development of selected tourist activitiesonsequently, based upon basic statistic information, the development and the structure of their accommodation facilities, beds, visitors, earnings, etc. are analysed while at the same time the most significant problems and disparities are pointed to. In the conclusion the possibilities of the development in the form of holiday models and their location within the evaluated territory of Eastern Slovakia are proposed.